Fases de Diseño, programación y pruebas de la nueva versión del Software Mercurio, para la empresa Servisoft S.A (2020)
The Servisoft company is a nationwide company dedicated to document management, the entity is the owner of the Mercurio software, it is currently in more than 300 companies in Colombia, since 1994 it offers small and large companies in both the public and private sectors the possibility to easily and effectively manage the documents and processes of the entities, currently technology is advancing and provides a better user experience compared to software tools, Servisoft wants to position and offer its clients a tool with the best technology, for this purpose in this project the procedure will be evidenced in the face of the entity's need, to implement a new version with new technological levels associated with the standards of usability, graphical interface, navigation and adaptability of the tool, among others.